If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + -12k = -4 Solving 22 + -12k = -4 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -12k = -4 + -22 Combine like terms: 22 + -22 = 0 0 + -12k = -4 + -22 -12k = -4 + -22 Combine like terms: -4 + -22 = -26 -12k = -26 Divide each side by '-12'. k = 2.166666667 Simplifying k = 2.166666667
| 15a=-45 | | 4y=6(1+y) | | -40(y-56)=y+(-36) | | 3a+1=-3.6-1/2 | | 1/x+2=0 | | 2x+1/y=3 | | 4x+1=-x+11 | | 3x+5(x-3)=49 | | -2+1=7w | | k/-5=12 | | 6(x+5)-30= | | 85-(4x+13)=4(x+9)+x | | 3x(6x-1)+2(2x-3)= | | 0.3x=0.6+0.4x | | 7+z=9 | | -2=-1+7w | | 1/5(5x-4)=7 | | (v^3/-2w)^3 | | 50=9l+18w | | 5=6+7w | | m+19=2m | | 43+x=2x | | x^4-6x^2-7x=6 | | 2(2*4.33-3)=4.33+7 | | (4v-7)(9+v)=0 | | 9-4x+3=3x+5 | | -(5/w-3)=-(5/4w-12)+1 | | 19/5=w | | 6x+9=99+4x | | 0.06(y-7)+0.02y=0.16y-0.05(20) | | 22=4-3m | | .18(y-7)+0.02=0.16y-0.03(40) |